2016
DOI: 10.1002/ps.4331
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptides from a novel Bacillus methylotrophicus 39b strain suppress Agrobacterium crown gall tumours on tomato plants

Abstract: B. methylotrophicus strain 39b exhibited antibacterial activity against phytopathogenic A. tumefaciens C58 and B6 both in vitro and in vivo. Lipopeptides are the main compounds that confer the biocontrol ability. This strain has the potential to be developed as a biological control agent for crown gall disease. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
(75 reference statements)
1
35
0
Order By: Relevance
“…Another solution relies on partnering cultureindependent studies with culture-dependent ones, i.e., community analysis and characterization of isolates, where dominant or differential bacteria can be selectively isolated for functional verification in vitro (37,41,42). Some culturable strains of Rhizobium, Pseudomonas, Bacillus, and Pantoea are successful biocontrol agents (43,44) or have high biological control potential against crown gall disease (30,(45)(46)(47)(48)(49)(50)(51)(52). In this study, similar genera were found to be strongly associated with pathogen invasion in a resistant peach cultivar, and some strains showed antagonistic activity via in vitro tests (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another solution relies on partnering cultureindependent studies with culture-dependent ones, i.e., community analysis and characterization of isolates, where dominant or differential bacteria can be selectively isolated for functional verification in vitro (37,41,42). Some culturable strains of Rhizobium, Pseudomonas, Bacillus, and Pantoea are successful biocontrol agents (43,44) or have high biological control potential against crown gall disease (30,(45)(46)(47)(48)(49)(50)(51)(52). In this study, similar genera were found to be strongly associated with pathogen invasion in a resistant peach cultivar, and some strains showed antagonistic activity via in vitro tests (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, the Bacillus methylotrophicus 39d strain has been proposed as a biological agent for crown gall disease in tomato plants. 5 Chemical and agronomical methods for controlling crown gall disease are only partially effective. 3,6 Germplasm evaluation is the first step towards breeding for crown-gall-resistant plants.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus methylotrophicus, well-studied Gram-positive bacteria, has previously been identified as plant growth promoting [2]. Nevertheless, few reports describe the isolation and characterization of its secondary metabolites; they are mainly lipopeptides [3]. In the course of our studies to detect novel bioactive substances from the hot soil microorganisms [4], herein we report the isolation, structural elucidation, and antimicrobial activity of five natural products from B. methylotrophicus ASWU-C2.…”
Section: Introductionmentioning
confidence: 95%